Chemical variability in volcanic gas plumes and fumaroles along the East African Rift System: new insights from the Western Branch - Boudoire, Guillaume; Giuffrida, Giovanni; Liuzzo, Marco; Bobrowski, Nicole; Calabrese, Sergio; Kuhn, Jonas; Mwepu, J. -C. Kazadi; Grassa, Fausto; Caliro, Stefano; Rizzo, Andrea Luca; Italiano, Francesco; Yalire, Matthieu; et al. (Chemical geology, 2022)
The origin of magmatic fluids along the East African Rift System (EARS) is a long-lived field of debate in the scientific community. Here, we investigate the chemical composition of the volcanic gas plume and fumaroles at Nyiragongo and Nyamulagira (Democratic Republic of Congo), the only two currently erupting volcanoes set on the Western Branch of the rift. Our results are in line with earlier conceptual models proposing that volcanic gas emissions along the EARS mainly reflect variable contributions of either a Sub-Continental Lithospheric Mantle (SCLM) component or a Depleted Morb Mantle (DMM) component, and deeper fluid. At Nyiragongo and Nyamulagira, our study discards a major contribution of a high 3He/4He mantle plume component in the genesis of volcanic fluids beneath the area. High CO2/3He in fumaroles of both volcanoes is thought to reflect carbonate metasomatism in the lithospheric mantle source. As inferred by previous results obtained on the lava chemistry, this carbonate metasomatism would be more pronounced beneath Nyiragongo. This supports the idea of the presence of distinct metasomes within the lithospheric mantle beneath the Western Branch of the rift.